Pengaruh Kemampuan Menganalisa dan Pembelajaran Berbasis Masalah (Problem Based Learning) Dengan Metode Rotating Trio Exchange Terhadap Prestasi Belajar Pada Mata Pelajaran IPS Ekonomi Kelas VII SMP Negeri 1 Todanan(Tahun ajaran 2015/2016) - Intan Paramita, Citra; , Dr. Djalal Fuadi, M.M (2016)
The aims of the research are (1) to know the effect of learning strategy to output (2) To know the effect of output from student analyze (3) To know there are relation between problem based learning program with rotating trio exchange that seen from skill of output analyze. This research include experimental research. The populate is all of the student of VII class of SMP Negeri 1 Todanan. The sample of this research is experimental group (problem based learning strategy with rotating trio exchange method), there are 38 students, while the control group are 37 students. So, total of sample are 75 students with cluster random sampling method. The method of collecting date are documentation, aangket, and test. The analyze of the date is using two way variation with different sel. The output of experimental are: (1) the output of study use problem based learning strategy with rotating trio exchange method is getting statistic F = 6,180 > F(0,05;1; 69) = 3,98. So, H₀ is reject. Arrange of rotating trio exchange is 57,509 , while the problem based learning is 50,946. So, the first hypothesis we know that the study with rotating trio exchange method better than problem based learning method. (2) The output of study bettweenproblem based learning and rotating trio exchange method to increase skill analyze, statistic F = 8,306 > F(0,05;2; 69) = 3,13, so H₀ is reject. The arrange of analyze use problem based learning with rotating trio exchange method is 57,42, while the arrange is use problem based learning with skill analyze is 56,73. It's means the second hypothesis we know that problem based learning with skill analyze is accept. (3) problem based learning strategy with rotating trio exchange method has statistic Fab = 12,032 > F(0,05;2; 69) = 3,13, So H₀ is reject. That means the three hypothesis has inferaction between learning strategy and skill analyze to output study.